ELECTRICAL INDUSTRY SAFETY: EXAMINING CONTROL STRATEGIES TO REDUCE ELECTRICAL RISKS BASED ON OSHA AND BLS (2011-2021) REPORTS - Azeez Olawale Ojelabi; Abdul Rohim Tualeka; Indriati Paskarini; Suardi Zurimi; Juliana Jalaludin (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: One essential component of contemporary society is the use of electricity in a variety of industrial sectors. However, its vital role brings inherent risks that demand strict adherence to safety precautions. Purpose: This literature review investigates and evaluates control measures implemented in the electrical industry to reduce risks and lower the incidence of electrical fatalities. The analysis focuses on the effectiveness of these control strategies and their alignment with the hierarchy of control framework. Review: This literature review employs a descriptive quantitative analysis. This study analyzes data from 2011 to 2021. During this period, the Bureau of Labor Statistics (BLS) reported 1.653 work-related electrical fatalities, while the Occupational Safety and Health Administration (OSHA) reported 1.201. Result: 118 vocations were linked to electrical fatalities during this time. Of these, 31% of deaths occurred in electrical-related jobs, while 69% happened in non-electrical jobs. This finding highlights the urgent need for comprehensive safety measures and effective control strategies to mitigate electrical hazards. Conclusion: This literature review highlights the importance of applying the Hierarchy of Controls (HOC) in managing electrical risks in the workplace. It calls for proactive interventions and a cultural shift toward prioritizing safety, integrating human awareness with strict regulations to reduce electricity-related fatalities.